Evaluation of Venous and Arterial Biochemical Factors Values in the Intensive Care unit Patients - Parviz Amri; Sarvin Seyfi; shahram Seyfi; Hoda Shirafkan (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: Patients admitted at the intensive care unit (ICU) need blood draws for chemistry analytes and arterial blood gas (ABG) analysis. Repeated blood drawing is one of the most common causes of anemia in these group of patients. Measurement of analytes only by ABG analyzer can be beneficial for preventing anemia. The aim of this study was to compare the biochemical analytes in venous and ABG samples in ICU patients. Materials and methods: This cross-sectional study was performed in 223 patients hospitalized in the ICU. These patients undergoing ABG analysis and simultaneous venous sampling. The value of Ca, Na, K, Hct, and glucose were measured in venous samples with a laboratory auto-analyzer and in arterial samples with an ABG analyzer. Results: The mean age of patients was 61.14±16.96 years. The mean difference between ABG and serum samples was 1.12 mEq/L for sodium, -0.29 mEq/L for potassium, -0.98 mg/dl for calcium, 0.33 mg/dl for glucose, and 4.39%% for hematocrit. In addition, 95% limit of agreement was -12.3 to 9 for sodium, -0.7 to 1.29 for potassium, -1.31 to 3.8 for calcium, -39.13 to 40.32 for glucose, and -13.5 to 8.5 for hematocrit. Conclusion: Because of acceptable agreement for sodium, potassium, and hematocrit, ABG analyzer can be used in ICU patients and emergency situations. There is a remarkable bias between the ABG-measured and laboratory-measured calcium and glucose, so the calcium and glucose measurement by the ABG analyzer are not reliable.